Money-Back Guarantees: Helping the Low-Quality Retailer - McWilliams, Bruce (Management Science, 2012)
Existing literature, based on signaling theory, suggests that money-back guarantees (MBGs) will be utilized by high-quality firms, where high quality is defined as a low likelihood of product return. However, in today's world, MBGs are ubiquitous among major retailers, even when the likelihood of product return varies greatly between them. To understand this phenomenon, we explore a competitive environment between high- and low-quality retailers where consumers are fully informed and risk neutral, and retailers realize a salvage value for returned products. When MBGs are profitable, under continuous demand it is Nash equilibrium for both retailers to offer MBGs, and the low-quality retailer gains while the high-quality retailer loses relative to when MBGs are not offered. In contrast, if demand is lumpy, retailers can act monopolistically over their respective market segments, allowing both retailers to gain from MBGs, although the low-quality retailer still gains more. This paper was accepted by J. Miguel Villas-Boas, marketing.